Konsep Administrasi Pendidikan - Annisa Rahmadani; Rizka Rahman Tanjung; Windi Melisa (Universitas 45 Surabaya, 2024)
Educational administration is an important field in the organization of effective and efficient education. This journal aims to discuss the basic concepts of educational administration, ranging from its definition, goals, functions, principles, to its scope. This journal discusses that educational administration is the process of managing educational resources to achieve educational goals. The main goal of educational administration is to improve the quality of education and produce quality graduates. The functions of educational administration include planning, organizing, directing, and supervising. The principles of educational administration that must be considered in its implementation are democratic, efficient, effective, and sustainable. The scope of educational administration includes personnel administration, curriculum administration, financial administration, facilities and infrastructure administration, student administration, and teaching and learning administration.